The role of dexmedetomidine in ARDS: an approach to non-intensive care sedation - Simioli, Francesca; Annunziata, Anna; Coppola, Antonietta; Imitazione, Pasquale; Mirizzi, Angela Irene; Marotta, Antonella; D’Angelo, Rossella; Fiorentino, Giuseppe (Frontiers in Medicine, 2023)
Introduction. Severe COVID-19 is a life-threatening condition characterized by complications such as interstitial pneumonia, hypoxic respiratory failure, and acute respiratory distress syndrome (ARDS). Non-pharmacological intervention with mechanical ventilation plays a key role in treating COVID-19-related ARDS but is influenced by a high risk of failure in more severe patients. Dexmedetomidine is a new generation highly selective α2-adrenergic receptor (α2-AR) agonist that provides sedative effects with preservation of respiratory function.The aim of this study is to assess how dexmedetomidine influences gas exchange during non-invasive ventilation (NIV) and high-flow nasal cannula (HFNC) in moderate to severe ARDS caused by COVID-19 in a non-intensive care setting.Methods: This is a single center retrospective cohort study. We included patients who showed moderate to severe respiratory distress. All included subjects had indication to NIV and were suitable for a non-intensive setting of care. 170 patients were included, divided in a control group (n=71) and a treatment group (DEX group, n=99).Results: 170 patients were hospitalized for moderate to severe ARDS and COVID-19. The median age was 71 years, 29% females. The median Charlson comorbidity index (CCI) was 2.5. Obesity affected 21% of the study population. The median pO2/FiO2 was 82 mmHg before treatment. After treatment, the increase of pO2/FiO2 ratio was clinically and statistically significant in the DEX group compared to the controls (125 mmHg [97 -152] versus 94 mmHg [75 -122]; ***p <0.0001). A significative reduction of NIV duration was observed in DEX group (10 [7 -16] days vs 13 [10 -17] days; *p <0.02). 24 patients required IMV in control group (n=71) and 16 patients in DEX group (n=99) with a reduction of endotracheal intubation of 62% (OR 0.38; **p <0.008). A higher incidence of sinus bradycardia was observed in the DEX group.Conclusion: dexmedetomidine provides a "calm and arousal" status which allows spontaneous ventilation in awake patients treated with NIV and HFNC. The adjunctive therapy with dexmedetomidine is associated with a higher pO2/FiO2, lower duration of NIV, and a lower risk of NIV failure. A higher incidence of sinus bradycardia needs to be considered.